Alternatives to Conventional Food Processing. - Proctor, Andrew, 1953- (Springer, 2010)
Annotation This multi-authored book is edited by an expert in the field and includes chapters from international contributors. It is fully cross disciplinary relating green principles to the food industry, covering legal and policy issues, engineering, food processing and food science. It addresses the alternatives to conventional food processing that have reduced energy requirements or solvent use and how they affect final food quality. Initially, the principles of green chemistry and technologies are outlined to provide a justification and basis for the processing methods that are addressed. This is followed by a discussion of legal and policy issues in both the EU and the US which provide further justification for the need for such technologies and the constraints and benefits of current policies and regulations. The major green technologies available to the food industry are discussed, outlining the main principles and applications of each. The degree to which they are already in commercial use and developments needed to extend their use further are also covered.
Keywords: Food industry and trade -- Environmental aspects.; Green chemistry.; elektronické knihy; electronic books